CONCENTRATIONS OF THE MAIN NUTRIENTS (N, P, K, B, ZN) IN FLAX SEED, STEMS AND CHAFF (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
During 1996-1998 experiments were carried out at the Lithuanian Institute of Agriculture’s Upyte Research Station to measure the contents of the main nutrients (N, P, K, B, Zn) accumulated in flax plants (seeds, stems and chaff) at harvesting on the following backgrounds: not fertilized, fertilized with P20 and N15P20K60; applied with ZnSO4 at the rates from 0,35 to 4,0 kg ha-1. It was determined that fibre flax seeds accumulated 3.30–4.06 % of N, 0.55–0.78 % of P, 0.69–1.15 % of K, 39.5–68.5 mg kg-1 of Zn, 10.00–27.00 mg kg-1 of B, the stems – 0.32–0.88 % of N, 0.04–0.15 % of P, 0.38–1.45 % of K, 5.0–18.0 mg kg-1 of Zn, 5.16–30.84 mg kg-1 of B, the chaff – 0.94–2.34 % of N, 0.20–0.38 % of P, 0.18– 1.40 % of K, 14.5–57.0 mg kg-1 of Zn, 8.55–38.19 mg kg-1 of B. The obtained data could be used for calculating the amount of main nutrients removed from the soil with flax yield as well as for fixing fertilizer rates more precisely.